Ergonomic design improvement at Koko Minda Food Industries (M) Sdn. Bhd - Roslam, Ahmad Nizamuddin; Zainuddin, Muhammad Amir Rahimi; Mamut, Muhammad Muhairie; Suriansah, Nur Lyana Syahirah; Basirun, Runizsyazrizan; Mahmood, Salwa; Tajurahim, Nurul Ainina Nadhirah; Ngadiman, Nor Hasrul Akhmal (Penerbit UTHM, 2020)
Koko Minda Food Industries (M) Sdn. Bhd was founded and established on year 2010 and still operating until now. This company is founded by Mr. Salim bin Salleh after he retired from working with government on year 2009. He decided to open up Koko Minda Food Industries (M) Sdn. Bhd because he has desired to continue working after being retired from working due to his sickness. His daughter, Ms. Nurul Firdaus binti Salim also giving hands to help him and serve as the Director of Administration & Marketing to run Koko Minda Food Industries (M) Sdn. Bhd. This company is located at IKS Halal Hub Serkam, Merlimau, Malacca, Malaysia and will be relocated to a new factory which 200 meters from its current factory.